Ocular bacterial infections: Pathogenesis and diagnosis. (August 2020) - Deepthi, KrishnanNair Geetha; Prabagaran, Solai Ramatchandirane
Abstract: The human eye is a rigid asymmetric structure with unique defence system. Despite considerable resident microbiota, eye is exposed to external environment where a range of microorganisms also inhabits. Opportunistically, some of these microorganisms could associate with eye pathogen that could contact incidentally, leading to destructive visual consequences. Among such microbiota, bacteria form the major proportion concerning ocular complications worldwide. The succession of genome based approach through 16S rRNA gene based identification tremendously augmented the knowledge on diversity of ocular surface bacteria. Such evidence suggests that while few bacteria contribute towards normal ocular functions, considerable number of bacteria play active role in pathophysiology of ocular diseases. Thus, understanding the complexity of ocular microflora not only throw light on their critical role towards normal function of the eye, but also enlighten on certain visual exigencies. Under these circumstances, development of a rapid, reliable and cost effective method is essential that eventually evolve as a routine diagnostic protocol. Such precise prognostic modalities facilitate ophthalmologists to formulate pioneering therapeutics towards challenging ocular diseases. Highlights: The human eye is colonized by a consortium of microbiota. Bacteria as major contributor in variety of ocular infections. Advancement in molecular techniques shown promise for early detection and mitigation of ocular infections.